Enhancing Food Security: Chlorophyll B Content in Several Rice Genotypes as an Indicator of Drought Stress Tolerance - Cahyani, Elsa Gafira; Azzahroh, Elsa Qonita; Fendiyanto, Miftahul Huda; Pratami, Mentari Putri (MUNISI: Military Mathematics and Natural Sciences, 2025)
Drought stress poses a major challenge in rice cultivation, particularly in dryland areas, as it inhibits plant growth and significantly reduces yield. Rice plants that are not drought-tolerant often suffer damage during critical growth phases, necessitating the development of rice varieties that possess resilience to drought stress to ensure food security. This study aims to identify rice genotypes with the highest chlorophyll B content, which may be more resistant to drought conditions, allowing them to be developed as superior varieties in water-scarce areas. The experiment involved measuring the highest chlorophyll B content in each test plant with three replications. Subsequently, the data were correlated with physiological traits such as leaf length, leaf count, and root length. We found that the highest chlorophyll B content was observed in the Inpago 5 rice variety, which positively correlated with leaf length, leaf width, and plant height. Therefore, chlorophyll B content can be used as an indicator of drought stress resistance in rice.